2018
DOI: 10.1523/eneuro.0059-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Novel Quantitative Analyses of Spontaneous Synaptic Events in Cortical Pyramidal Cells Reveal Subtle Parvalbumin-Expressing Interneuron Dysfunction in a Knock-In Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder that has become a compelling global public health concern. Besides pathological hallmarks such as extracellular amyloid plaques, intracellular neurofibrillary tangles (NFTs), and loss of neurons and synapses, clinical reports have shown that epileptiform activity, even seizures, can occur early in the disease. Aberrant synaptic and network activities as well as epileptiform discharges have also been observed in various mouse models of AD. The new AppNL-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 67 publications
(103 reference statements)
1
26
0
Order By: Relevance
“…Our findings indicate an age-dependent increase in Aβ1–42 levels and plaque deposition that are consistent with previous research 19,21,32 . Previous reports indicated the absence of hyperexcitability in the App NL-G-F at 8 and 12 months of age 24 and subtle synaptic alterations at around 18 months 50 . However, other reports have indicated theta-gamma coupling impairments in the entorhinal cortex of App NL-G-F mice at 5 months of age 51 and hypersynchronous functional connectivity of brain networks using resting-state functional MRI in App NL-G-F mice at 3 months (pre-plaque stage) 52 .…”
Section: Discussionmentioning
confidence: 85%
“…Our findings indicate an age-dependent increase in Aβ1–42 levels and plaque deposition that are consistent with previous research 19,21,32 . Previous reports indicated the absence of hyperexcitability in the App NL-G-F at 8 and 12 months of age 24 and subtle synaptic alterations at around 18 months 50 . However, other reports have indicated theta-gamma coupling impairments in the entorhinal cortex of App NL-G-F mice at 5 months of age 51 and hypersynchronous functional connectivity of brain networks using resting-state functional MRI in App NL-G-F mice at 3 months (pre-plaque stage) 52 .…”
Section: Discussionmentioning
confidence: 85%
“…In addition, SST interneurons such as oriens lacunosum-moleculare (O-LM) cells show enhanced responses to theta frequency inputs (Pike et al 2000;Zemankovics et al 2010;Whittington and Traub 2003), while PV interneurons such as basket cells show enhanced responses to gamma frequency inputs (Pike et al 2000;Zemankovics et al 2010), further indicating their cell type-specific involvement in theta and gamma oscillations. Recent experimental evidence revealed that SST and PV interneurons disintegrate structurally and functionally in mouse models of AD (Palop et al 2007;Schmid et al 2016;Chen et al 2018;Verret et al 2012;Martinez-Losa et al 2018;Iaccarino et al 2016), suggesting that dysfunctions of SST and PV interneurons may underlie impairments of theta and gamma oscillations observed in AD. Optogenetic activation (Iaccarino et al 2016) or molecular manipulation (Martinez-Losa et al 2018;Zhang et al 2017) of PV interneurons could restore impaired hippocampal gamma oscillations in mouse models of AD.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Fewer studies exist of second-generation APP knock-in models which address the APP overexpression problem, yet have less pronounced disease phenotypes (Sasaguri et al, 2017). In one relevant study, sIPSC amplitude from putative PV cells is decreased in parietal cortex PCs from 18-to 20-month App NL-F mice, although synaptic E/I balance is unchanged (Chen et al, 2018). It will be critical to study hippocampal network alterations, both at the level of the microcircuit and behaving animal, in novel AD mouse models with greater validity.…”
Section: Swr Alterations In Aging and Diseasementioning
confidence: 99%